Poor hDNA-Derived NGS Data May Provide Sufficient Phylogenetic Information of Potentially Extinct Taxa - Clewing, Catharina; Kehlmaier, Christian; Stelbrink, Björn; Albrecht, Christian; Wilke, Thomas (Frontiers in Ecology and Evolution, 2022)
Museum material is an important source of metadata for past and recent biological events. With current sequencing technologies, it is possible to obtain historical DNA (hDNA) from older material and/or endangered species to answer taxonomic, systematic and biogeographical questions. However, hDNA from museum collections is often highly degraded, making it difficult to assess relationships at or above the species level. We therefore studied two probably extinct gastropod species of the genus Laevicaspia, which were collected ~140 years ago in the Caspian Sea, to map ‘standard’ mitochondrial and nuclear markers and assess both the sequencing depth and the proportion of ambiguous sites as an indicator for the phylogenetic quality of the NGS data. Our study resulted in the first phylogenetically informative mitochondrial and nuclear markers for L. caspia. Assessment of both sequencing depth (mean coverage) and proportion of ambiguous sites suggests that our assembled consensus sequences are reliable for this species. In contrast, no informative gastropod-specific DNA was obtained for L. conus, likely due to a high degree of tissue digestion and contamination with non-gastropod DNA. Nevertheless, our results show that hDNA may in principle yield high-quality sequences for species-level phylogenetic analyses, which underlines the importance of museum collections as valuable archives of the biological past.